Optimization of Laser Process Parameters and Improved Corrosion Behavior of Ytterbium Silicate Environmental Barrier Coating - Avci, Ali; Karabas, Muhammet; Sayar, Muhammet Halit; Akman, Erhan; Kucukyildirim, Bedri Onur; Akdogan Eker, Aysegul (SPRINGER, 2026)
Environmental barrier coatings (EBCs) were developed to protect SiC/SiC CMCs used in the hot sections of new-generation gas turbine engines from corrosion. Plasma-sprayed YbSi is deposited as an EBC top layer, mostly in the amorphous phase. Plasma spraying inherently creates cracks and porosity on the surface. These are disadvantages of coatings in hot corrosion and CMAS corrosion. To address these disadvantages, the presented study explored laser glazing as a solution. The surfaces of plasma-sprayed EBCs were modified with various laser processing parameters. The entire surface of the EBC was glazed using the determined optimum parameter. Hot corrosion and CMAS corrosion tests were conducted on laser-glazed EBCs. Laser glazing transformed the amorphous phase structure of the YbSi into a crystalline. It also created a smooth and dense layer on the surface. Characterizations after hot corrosion tests showed that the laser-modified sample did not show enhanced resistance. Structural deterioration, specifically an induced crack network and pits, facilitated increased penetration of corrosive salts. This led to a degradation of performance compared to the as-sprayed coating, which maintained partial resistance. Conversely, laser modification proved highly beneficial for CMAS corrosion of EBCs. The fully scanned surface's crystallized structure effectively restricted the penetration of the corrosive glass phases. This structural integrity and the maintenance of the Yb2Si2O7 phase stability resulted in a 50% enhancement in corrosion resistance, significantly reducing the passage of corrosive salts through the coating section relative to the as-sprayed sample. In conclusion, laser surface modification successfully achieved the desired crystallization, which is crucial for excellent performance in CMAS environments but simultaneously detrimental to hot corrosion resistance due to associated structural issues. Further optimization of laser parameters or coating composition is necessary to mitigate the structural defects that compromise hot corrosion performance.
Keywords: CMAS; environmental barrier coatings; hot corrosion; laser surface modification; RESISTANCE; SURFACE; OXIDATION; CERAMICS; DEGRADATION; YB2SI2O7; ATTACK; YSZ; Materials Science